2020
DOI: 10.33545/26164485.2020.v4.i2a.147
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disorder and their homoeopathic management

Abstract: Endocrine disorder acts as a vital issue in the modern era. Endocrine system plays an important role in human being for maintaining physiological as well as vital events, which makes a smooth relationship between body and mind. The disorder of such glands makes imbalance in both physically as well as mentally. In the modern era to run sophisticated life must stay healthy and makes your gland healthy. Homoeopathy is the system by which you stay healthy and makes your generation healthy. Homoeopathy acts as a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…A careful review of homoeopathic literature showed us the scope of management of hypothyroidism with homoeopathy because of its rich clinical and therapeutic material [4] . Endocrine disorders like hypothyroidism are often hereditary or having constitutional defects [5] . Homoeopathy plays a role in such conditions because the remedy selection depends on individual totality.…”
Section: Diagnosismentioning
confidence: 99%
“…A careful review of homoeopathic literature showed us the scope of management of hypothyroidism with homoeopathy because of its rich clinical and therapeutic material [4] . Endocrine disorders like hypothyroidism are often hereditary or having constitutional defects [5] . Homoeopathy plays a role in such conditions because the remedy selection depends on individual totality.…”
Section: Diagnosismentioning
confidence: 99%